2022
DOI: 10.11591/ijere.v11i3.22399
|View full text |Cite
|
Sign up to set email alerts
|

The spatial thinking process of the field-dependent students in reconstructing the geometrical concept

Abstract: <p><span lang="EN-US">Reconstructing geometrical concepts requires a spatial thinking process, so the spatial thinking process will be correct and complete. The phenomena of cognitive style differences cause different perceptions and thinking activities to solve geometric problems. This qualitative-explorative research describes the spatial thinking process of students with field-dependent cognitive styles in reconstructing the concept of spatial geometry based on the theory of Action-Process-Objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Their results showed that individuals' predisposition towards field independence predicted higher performance on mental rotation and perspective-taking tasks. Bintoro et al [35] studied how the field dependency of high school students influences their spatial thinking process. Their results demonstrated that FD students have difficulty creating spatial representation and exhibit the inaccuracy of spatial thinking.…”
Section: Cognitive Style and Spatial Abilitymentioning
confidence: 99%
“…Their results showed that individuals' predisposition towards field independence predicted higher performance on mental rotation and perspective-taking tasks. Bintoro et al [35] studied how the field dependency of high school students influences their spatial thinking process. Their results demonstrated that FD students have difficulty creating spatial representation and exhibit the inaccuracy of spatial thinking.…”
Section: Cognitive Style and Spatial Abilitymentioning
confidence: 99%
“…In this process, students apply their observational findings from the practicum to bolster their existing theoretical knowledge, thereby constructing a robust conceptual framework [11][12][13][14]. The significance of engaging in practicum activities in the context of science education is underpinned by four pivotal reasons [15]. Firstly, it elevates students' motivation to delve into scientific subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive style is a person's thinking ability to process, store and use to respond to information (Bassey et al, 2009;Ratuanik, 2018). Cognitive style is a variable that teachers must pay attention to in designing learning because cognitive style can influence the way students learn and the way students interact with teachers in the classroom (Bintoro et al, 2022).…”
Section: Introductionmentioning
confidence: 99%